2021
DOI: 10.1021/acs.energyfuels.1c01995
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of CO2 with Utica, Marcellus, Barnett, and Eagle Ford Shales and Impact on Permeability

Abstract: In order to reduce greenhouse gas emissions while recovering hydrocarbons from unconventional shale formations, processes that make use of carbon dioxide to enhance oil recovery while storing carbon dioxide (CO2) should be considered. Here, we examine samples from three shale basins across the United States (Utica and Marcellus Shales in the Appalachian Basin, Barnett Shale in the Bend Arch-Ft. Worth Basin, and Eagle Ford in the Western Gulf Basin) to address the following questions: (1) do changes from reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…It is self-explanatory that, for the progress of civilization, utilization of available energy resources cannot be terminated, and to accommodate this with the PCA objective, negative GHG emissions is to be achieved in the coming decades. Luderer et al estimated that, even after phenomenal efforts by several countries, the fossil fuel contribution to emission until the end of century would remain ∼1000 Gt CO 2 . In this context, carbon capture and storage (CCS) in geological reservoirs has been identified as a feasible near-term option to combat the rising GHG emissions. ,− …”
Section: Introductionmentioning
confidence: 99%
“…It is self-explanatory that, for the progress of civilization, utilization of available energy resources cannot be terminated, and to accommodate this with the PCA objective, negative GHG emissions is to be achieved in the coming decades. Luderer et al estimated that, even after phenomenal efforts by several countries, the fossil fuel contribution to emission until the end of century would remain ∼1000 Gt CO 2 . In this context, carbon capture and storage (CCS) in geological reservoirs has been identified as a feasible near-term option to combat the rising GHG emissions. ,− …”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the distribution of wells in the field, where eight horizontal wells were completed in the Eagle Ford between 2011 and 2013, as shown by the black line in Figure . Similar to the Bakken, the Eagle Ford formation has an extremely tight rock matrix, where the permeability is at a nano-darcy to micro-darcy level. The crude oil produced from Eagle Ford shale is also volatile because of the high percentage of light components in the oil. , At this site, the oil production rate dropped nearly 90% in the first 5 years of production, from a peak rate of 40,863 bbl/month (6.5 × 10 3 m 3 /month) (in August 2011) to 4500 bbl/month (0.715 × 10 3 m 3 /month) (in April 2016).…”
Section: Assessment Of Immiscible and Miscible Field Casesmentioning
confidence: 94%
“…A variety of laboratory experiments and simulation studies were performed to investigate EOR mechanisms and predictive potential EOR responses in unconventional reservoirs. ,, However, very few of these studies were correlated with actual field performance. One of the reasons was the limited access to actual field data. , In this section, a series of experiments were collected for gas injection pressure, MMP, and oil recovery factor assessment in the Bakken and Eagle Ford, and then a set of new experimental and simulation activities were carried out to correlate the laboratory/simulation observations with actual field performance.…”
Section: Laboratory and Simulation Investigationsmentioning
confidence: 99%
“…In addition, CO 2 adsorption induced swelling will decrease the permeability of shale. , Thus, the permeability of a shale gas reservoir is influenced by multiple factors, leading to diversified complex characteristics in the permeability evolution of shale. Some researchers have found that the permeability of shales increased after CO 2 exposure and increased with increasing reaction time, temperature, and pressure. , However, other researchers argue that the permeability of shale decreased with the increase of CO 2 exposure time, and the reduction of permeability caused by ScCO 2 is stronger than that caused by SubCO 2 . ,, It is obvious that there are two distinct and opposite variation trends of permeability in shale, which can be interpreted by the different experimental conditions for them and the difference in dominant factors for the different shales. On the one hand, the extraction and dissolution effects of CO 2 exposure play dominant roles in permeability variation; thus the permeability showed an increasing trend after CO 2 exposure.…”
Section: Alterations In Physical and Chemical Properties Of Shalementioning
confidence: 99%